2006
DOI: 10.1111/j.1574-6941.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of biofilm bacteria in modulating the larval metamorphosis of Balanus amphitrite

Abstract: Natural microbial communities found on different substrata exposed to the marine environment, including barnacle shell surfaces, are reported to have varying influences on the settlement and metamorphosis of competent cypris larvae. Experiments were carried out to compare the influence of settlement-inducing compounds from the bacteria isolated from the shell surface of Balanus amphitrite on its larval metamorphosis. The effect of multispecies bacterial film was also assessed. The production of different molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 40 publications
2
37
0
1
Order By: Relevance
“…Those results highlighted the importance of water soluble chemical cues as settlement inducers for P. canaliculus larvae. Studies with other marine invertebrate species have resulted in similar findings (Bao et al, 2007a;Fitt et al, 1990;Khandeparker et al, 2006;Neumann, 1979;O'Connor and Richardson, 1998;Satuito et al, 1997). In the present study, the settlement inducing fractions for P. canaliculus larvae were found to be of 1-3, 3-10 and 10-30 kDa for Macrococcus sp.…”
Section: Discussionsupporting
confidence: 88%
“…Those results highlighted the importance of water soluble chemical cues as settlement inducers for P. canaliculus larvae. Studies with other marine invertebrate species have resulted in similar findings (Bao et al, 2007a;Fitt et al, 1990;Khandeparker et al, 2006;Neumann, 1979;O'Connor and Richardson, 1998;Satuito et al, 1997). In the present study, the settlement inducing fractions for P. canaliculus larvae were found to be of 1-3, 3-10 and 10-30 kDa for Macrococcus sp.…”
Section: Discussionsupporting
confidence: 88%
“…Barnacle cyprids other than their conspecifics also settle on the substrata that possess a well‐developed biofilm (Harder, Thiyagarajan & Qian, 2001; Khandeparker, Anil & Raghukumar, 2002 b , 2006). Bacteria produce surface‐bound and soluble chemical cues that either stimulate or inhibit larval settlement (Maki et al , 1990; Unabia & Hadfield, 1999; Qian et al , 2003; Dobretsov, Dahms & Qian, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Khandeparker et al (2006) suggested that bacteria-adult extract interaction can alter the synthesis of compounds produced by bacteria. When the natural biofilm was assessed along with the adult extract the cyprid metamorphosis increased significantly.…”
Section: Discussionmentioning
confidence: 99%